Preparation Optimization, Characterization, and Antioxidant and Prebiotic Activities of Carboxymethylated Polysaccharides from Jujube - Runfang Feng; Jingjing Kou; Shan Chen; Na Wang; Weiwei Wang; Lili Wang; Huiqiang Wang; Christopher Ference; Mengjun Liu; Changwei Ao; Zhihui Zhao (Journal of Food Quality)
In this study, jujube polysaccharides (JP) were extracted from Jinsixiaozao, and carboxymethylated jujube polysaccharides (CMJP) were prepared. The optimum carboxymethylation conditions optimized by Response Surface Methodology (RSM) were as follows: the reaction temperature was 60°C, the concentration of sodium hydroxide (NaOH) solution was 2.8 mol/L, and the content of chloroacetic acid was 2.12% with a degree of substitution (DS) of 0.2275 ± 0.0108. Physicochemical characterizations and in vitro antioxidant and prebiotic activities of JP and CMJP were evaluated. Compared with unmodified JP, water solubility and viscosity were improved in CMJP. Chemical analysis revealed that CMJP was composed of Rha: Ara: Xyl: Glc: Gal = 0.18 : 9.09 : 0.45 : 0.36 : 0.98 with a molecular weight of 3.04 × 105 Da. The signals of carboxymethyl were observed at 1600, 1420, and 1328 cm−1 in FT-IR. In addition, CMJP showed obviously strong hydroxyl radical scavenging ability compared with JP and also exhibited stronger abilities than JP on the proliferation growth of Lactobacillus acidophilus, Lactobacillus plantarum, and Lactobacillus rhamnosus strains. These results indicated that CMJP could be explored as a promising resource for the development of functional foods.